Preference of Santri in Increasing Interest of Saving at Sharia Banks in Malang Regency : Study at Islamic Boarding School of Annur Bululawang - Roisul Adib (Iqtishodia: Jurnal Ekonomi Syariah, 2021)
At present the sharia banking sector is experiencing relatively rapid growth. Islamic banking is able to show high acceleration of growth with an average growth of 40.20% per year in the last five years (2015-2020). While the average national banking growth was only 16.7%. Therefore, Islamic banking is nicknamed "The fastest growing industry". This rapid growth can be seen from the financial ratios of Islamic banks which show that Islamic banks have a good level of health. Of course there are some things that need to be known to cause an increase in financial ratios including knowledge, religiosity, bank products and services. This study aims to determine the preferences of students saving interest towards Islamic banks. This research method is quantitative research with data analysis techniques using Correlation Research using SPSS software. Data collection uses stratified random sampling by taking 81 samples from various strata. The results of this study indicate that there is an influence of Knowledge, Religiosity, Bank Products, Services on students' interest in saving students, which means the hypothesis is accepted.